Compreensão de leitura em textos multimodais impressos e suportados pelo computador: uma abordagem cognitivo-textual - Cavalcante, Liliane Carvalho Félix (2010)
This research deals with reading comprehension as a result of several integrated cognitive processes . It discusses the relationship of the dynamics of cognitive activities that support the preparation of these idealized cognitive models from reading texts. To consider this issue, the understanding was investigated through experiments and instruments in which observed variables: cognitive strategies and prior knowledge, using the hypothetical-deductive method. The study was conducted with students of the first and second grade of a technical course of ensino médio integrado in computering. The experiment consisted of multimodal texts in two ways: digital (hypertext) and printed. Control the rate of multimodality in this text in order to observe the effect of this factor in the variables mentioned. The instruments used were questionnaires and tests of problem solving applied after reading the texts. Keywords: reading comprehension, multimodality, idealized cognitive models. As evaluation tools we confronted the students' answers, which we call MCI qualis with expectations or prototypes of the author, who named MCI expert. To address this phenomenon, we sought theoretical support in the theories: Idealized Cognitive Models of Lakoff (1987), Conceptual Categories, by Lakoff and Johnson (1980), Mental Spaces in Faucconier and Sweetser (1996), Conceptual Integration Networks, in Faucconier and Turner (2002), in studies of reading, Kleimann (2004), and processing of reading, Kato (2007). The results indicate that the constitution of MCI qualis, or reading comprehension, can be conditioned by the presence and role of cognitive strategies and prior knowledge that are evoked in the processing of reading, and that the text in digital does not imply a higher conditioning understanding, whereas the presence of multimodality, both in printed and digital favors the availability of cognitive activities that culminate in a greater degree of understanding.